Moisture analysis and condensation control in building envelopes - Trechsel, Heinz R. (ASTM, 2001)
Annotation Contributors address typical moisture analysis methods and models and provide the technical background for understanding and applying moisture analysis. Chapters address weather data, hygrothermal properties of building materials, failure criteria, an overview of hygrothermal analysis methods (HAM), advanced numerical models for hygrothermal research, manual analysis tools, a numerical method for design, and a hygrothermal design tool for architects and engineers. Includes a glossary and instructions for using the CD-ROM, which includes two models of computer-based moisture analysis, as well as two programs to convert various properties of air. Annotation c. Book News, Inc., Portland, OR (booknews.com).
"ASTM stock number: MNL40."
Keywords: Waterproofing.; Dampness in buildings.; Exterior walls.; elektronické knihy; electronic books